2006
DOI: 10.1038/sj.bmt.1705247
|View full text |Cite|
|
Sign up to set email alerts
|

Risk and prognostic factors for Japanese patients with chronic graft-versus-host disease after bone marrow transplantation

Abstract: The incidence and prognostic factors for chronic graftversus-host disease (cGVHD) were evaluated for 255 Japanese patients who survived more than 100 days after bone marrow transplantation, and of whom 119 (47%) developed cGVHD. Prior acute GVHD (grade 2-4) and use of an unrelated donor were significantly associated with the onset of cGVHD. Presence of cGVHD did not have an impact on mortality (hazard ratio (HR) ¼ 0.89; 95% confidence interval (CI), 0.59-1.3). Three factors at diagnosis were associated with cG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 19 publications
(42 reference statements)
5
25
4
2
Order By: Relevance
“…Grade II-IV acute GVHD occurrence was a strong risk factor for chronic and extensive chronic GVHD, regardless of the donor type, which is consistent with previous findings. [4][5][6][7] The mechanism through which chronic GVHD develops is considered to be different from that of acute GVHD, 28 and the underlying mechanism by which acute GVHD strongly influences chronic GVHD development remains unknown. Acute GVHD causes thymic epithelial damage and functional deterioration, leading to a decrease in thymic output, represented by low T-cell receptor excision circle levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade II-IV acute GVHD occurrence was a strong risk factor for chronic and extensive chronic GVHD, regardless of the donor type, which is consistent with previous findings. [4][5][6][7] The mechanism through which chronic GVHD develops is considered to be different from that of acute GVHD, 28 and the underlying mechanism by which acute GVHD strongly influences chronic GVHD development remains unknown. Acute GVHD causes thymic epithelial damage and functional deterioration, leading to a decrease in thymic output, represented by low T-cell receptor excision circle levels.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Several studies have reported a history of acute GVHD to be a strong risk factor that is consistently associated with chronic GVHD development. [4][5][6][7][8] Other identified risk factors include the following: female donor and male recipient, 4,6 use of PBSC grafts, 6,9-13 older patient, 4,[6][7][8] older donor, 6,7 transplantation from a mismatched or unrelated donor, 5,6,14 diagnosis of CML 4,7,8 and absence of anti-thymocyte globulin (ATG) use. 15 The number of unrelated cord blood (U-CB) transplantations performed has rapidly increased during the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…4,22 Atsuta et al 22 reported that prognostic scoring systems, which were developed on the basis of clinical findings for western patients, did not produce an effective categorization for Japanese patients. The proportion of a progressive type onset of chronic GVHD in Japanese patients is much lower than that in western countries, and the extent of cutaneous chronic GVHD was also different.…”
Section: Discussionmentioning
confidence: 99%
“…A history of acute GVHD is known to be a strong risk factor for chronic GVHD development, [21][22][23][24] and other risk Values are n (%) unless otherwise specified.…”
Section: Discussionmentioning
confidence: 99%
“…factors include a female donor to a male recipient, 22,23 the use of PBSCs, 25,26 older donor and recipient, 21,23 mismatched or unrelated donor, 23 no use of antithymocyte globulin 27 and CML. 22,24 Regarding risk factors for ocular GVHD, several studies have suggested that prior acute skin GVHD was an independent predictor for ocular GVHD, 10,12 and we also observed that skin involvement during the acute and chronic stages was correlated with the onset of ocular GVHD.…”
Section: Discussionmentioning
confidence: 99%